Dissipative Boussinesq system of equations in the Bénard-Marangoni phenomenon - Kraenkel, R. A. [UNESP]; Kurcbart, S. M. [UNESP]; Pereira, J. G. [UNESP]; Manna, M. A. (American Physical Society (APS), 1994)
By using the long-wavelength approximation, a system of coupled evolution equations for the bulk velocity and the surface perturbations of a Bénard-Marangoni system is obtained. It includes nonlinearity, dispersion, and dissipation, and it can be interpreted as a dissipative generalization of the usual Boussinesq system of equations. As a particular case, a strictly dissipative version of the Boussinesq system is obtained. © 1994 The American Physical Society.